Pelatihan Social Media Marketing untuk Anggota Komunitas Sisi Lain Kabupaten Tegal Bandung Raya (SLKT Baraya) - Miftakhul Fikri; Dimyati, Dindin; Rozaq, Miftahul; Nuraeni, Reni; Hadiansah, Ihsan (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
This training aims to provide practical knowledge and skills in managing social media as a tool to develop a business. For Warung Tegal (Warteg) business actors in Bandung City, the ability to utilize social media as a business platform is a very important skill. Through social media, warteg products and services can be promoted widely without geographical limitations. The Sisi Lain Community of Tegal Bandung Raya Regency (SLKT Baraya) has great potential to be empowered. Its potential lies not only in the individual abilities of its members but also in the collective strength of the community in creating social and economic impacts for the people. The training stages are specifically designed for members of the Sisi Lain Community of Tegal Bandung Raya Regency (SLKT Baraya) including the preparation stage, implementation stage, practice stage, and closing stage. This training is expected to help members of the SLKT Baraya community understand how to utilize various social media platforms to reach a wider target market.